2019
DOI: 10.1097/txd.0000000000000964
|View full text |Cite
|
Sign up to set email alerts
|

Late Conversion From Calcineurin Inhibitors to Belatacept in Kidney-Transplant Recipients Has a Significant Beneficial Impact on Glycemic Parameters

Abstract: Background. Calcineurin inhibitors (CNIs) and steroids are strongly associated with new-onset diabetes after transplantation, worsening of pre-existing diabetes, and cardiovascular events. We assessed the benefit of conversion from CNI-based to belatacept-based immunosuppression in diabetic kidney-transplant (KT) recipients on glucose control and cardiovascular risk factors. Methods. In this retrospective, noncontrolled single-study conducted between Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…The tacrolimus‐treated kidney transplant recipients had lower insulin release in the presence of higher insulin sensitivity, when compared to belatacept‐treated kidney transplant recipients. The study also confirmed a lower PTDM rate with belatacept, compared to tacrolimus [62], which has recently been observed in another retrospective study [63]. The tacrolimus‐belatacept comparison represents new information, as the available literature had previously only suggested superiority of belatacept, in terms of a reduced PTDM incidence [64,65], when this immunosuppressive agent was compared to cyclosporine.…”
Section: Management Of Ptdm: Immunosuppressionsupporting
confidence: 77%
“…The tacrolimus‐treated kidney transplant recipients had lower insulin release in the presence of higher insulin sensitivity, when compared to belatacept‐treated kidney transplant recipients. The study also confirmed a lower PTDM rate with belatacept, compared to tacrolimus [62], which has recently been observed in another retrospective study [63]. The tacrolimus‐belatacept comparison represents new information, as the available literature had previously only suggested superiority of belatacept, in terms of a reduced PTDM incidence [64,65], when this immunosuppressive agent was compared to cyclosporine.…”
Section: Management Of Ptdm: Immunosuppressionsupporting
confidence: 77%
“…To our knowledge, only one publication has recently provided data on differences in glucose metabolism between tacrolimus and belatacept-treated patients. 9 This retrospective study on 112 KTRs transplanted for ≥6 months, who were thereafter converted to belatacept for nephroprotection, identified an improvement in HbA1c levels in diabetic and nondiabetic KTRs. 9 Changes in insulin secretion and/or sensitivity were unfortunately not reported.…”
Section: To the Editormentioning
confidence: 92%
“…9 This retrospective study on 112 KTRs transplanted for ≥6 months, who were thereafter converted to belatacept for nephroprotection, identified an improvement in HbA1c levels in diabetic and nondiabetic KTRs. 9 Changes in insulin secretion and/or sensitivity were unfortunately not reported. 9 These findings are limited by the possibility of confounding due to differences between the groups at baseline and during follow-up, especially worse kidney function and lower magnesium levels among tac-KTRs.…”
Section: To the Editormentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, in the BENEFIT study, after a 7-year follow-up, patient-and graft-survival rates were significantly higher in patients treated with belatacept compared to those treated with cyclosporine [8]. Recently, we have shown that a late switch from CNIs to belatacept was a valuable therapeutic option for diabetic kidney-transplant recipients and substantially improved glycemic parameters [12]. Lastly, belatacept has also shown potential benefits by lowering the appearance of de novo donor-specific alloantibodies (DSAs) after KT and by decreasing pre-existing DSAs [13,14].…”
Section: Introductionmentioning
confidence: 99%